Compreender como os profissionais de enfermagem experimentam o mundo da vida e reflexos nas boas práticas assistenciais em uma Unidade de Terapia Intensiva - Queiroz, Patrícia Aquino de (2023)
The intensive care unit (UTI) is recognized as a restricted care environment, with high technological density and high complexity, as it treats ill patients at imminent risk of death. The intensive care nurse acts as coordinator of the nursing team and, together with the team (nursing technicians and other professionals) and provide essential care to maintain life. However, in addition to clinical practice, the UTI environment exposes nursing professionals to stressful situations arising from exhausting working hours, low pay, high complexity, and lack of resources, which directly may affect the quality, safety of care and health outcomes, also promoting harmful effects on the physical and mental health of professionals. This study aims to understand the perception of nursing professionals about the challenges experienced in the professional performance of safe care processes in intensive care units. This is a qualitative, interpretative study from the theoretical perspective of Symbolic Interactionism, anchored to the methodological framework of Grounded Theory (GT), with nurses and nursing technicians working in Intensive Care Units of a federally managed university hospital. From the stages of analysis of the collected data, the categories emerging from the codification and analysis process are described: Motivation and professional choice, Difficulties in articulating work with personal life, The relationship and communication between professional and institution, Communication between teams and the relationship with assistance, Reflections and possibilities of recognition. From the correlation of phenomena and categories found in the paradigmatic model, the central phenomenon emerged: safe care is the result of a significant interaction of the self with the team and institution. The relationship between the categories mentioned above allowed the establishment of the integration and understanding of the phenomena. The findings show complaints related to overload, stress and accumulation of functions, together with the neglect of personal aspects, such as leisure, spirituality and self-care demands, which affects the perception of happiness and satisfaction of nursing professionals. However, despite the negative feelings, they show realization about their current job and professional career, considering the institution and the manager-employee relationship as healthy. Regarding routines, participants refer to effectiveness in implementing protocols and following established goals, especially with regard to the prevention of infections associated with health care. Teamwork was highlighted as a potentiality, based on the articulation of the nursing team with the multidisciplinary team, in the face of weaknesses, such as poor communication, fatigue and emotional problems related to the ICU environment, in addition to obstacles in the process of professional qualification and instability of working arrangements. From the conduct of the study, possibilities for innovation and improvement are visualized, based on the implementation of training, professional updating, incorporation of technologies, as well as the forecast of resources, whether material or human, in favor of improving the effectiveness of communication between the team.